Degradation of The Lontara Script's Socio-Cultural Value among Millennial in Antang Village, Makassar City - Syahban Nur; Herdianty R.; Indah Ainun Mutiara (International Journal of Qualitative Research, 2021)
The people of Makassar, which are part of South Sulawesi, certainly have abundant cultural diversity, including the inheritance of character values and manners for the younger generation. Like the cultural conditions in general. Until now no one has been able to maintain the status quo of the culture itself. This study aims to determine: 1) How is the degradation of the socio-cultural values of Lontara characters such as the value of siri, pacce, sipakatau, reso among millennials in Antang Village. 2) What are the forms of changes in the socio-cultural value of the Lontara script among millennials in Antang Village. The research method used is descriptive qualitative often referred to as naturalistic research methods. The approach used in this research is the case study approach, the author uses the case study approach because an intensive empirical study investigating real life is carried out, the informants totaled five people with different backgrounds. Data collection techniques, namely observation, interviews, documentation. The data analysis technique uses descriptive-analytical methods, namely data reduction, data presentation, verification. The results of this study indicate that the community sees the character of the millennial generation as having undergone significant changes. The cultural values of the Lontara script have begun to be forgotten, even most of them only know and have minimal application in everyday life, this can be seen with the absorption of understanding modernism, pragmatism, materialism, secularism, hedonism, and ethnocentrism. As for the forms of changes in the socio-cultural value of the Lontara script, there is an attitude of individualism in the millennial generation, behaving at will, discriminating against, dependence, loosening of ties, feeling insecure and promiscuity, consumptive behavior, and a lack of understanding of the millennial generation of cultural understanding.